Study on the relationship between ecological environment and tourism industry development in Tai'an. Issue 1 (November 2020) - Zhang, Dongmei; Zhao, Weijun; Liu, Xiaomei; Yan, Tingting; Chen, Shilan
Abstract: As a special form of tourism, ecotourism is one of the important factors to realize the sustainable development of tourism. The relationship between ecological environment and tourism development is not very clear. Based on the development of forestry resources and using the methods of linear regression and correlation analysis, this study analyzed the development of tourism industry in Tai'an, such as forestry production, tourism reception volume, and the relationship between them. The results showed that: (1) the area of forestry resources in Tai'an was increasing at an annual rate of 37.4%; (2) during 2004-2009, the proportion of the tertiary industry in the GDP of Tai'an increased from 34.19% to 35.57%, and the tourist reception increased by 22.2% year on year; (3) there was a significant linear correlation between forestry resources and tourism development, and the functional relationship between them was y = 0.0383x - 2965.5, R 2 = 0.874. The results of this study can provide scientific reference for the sustainable development of ecotourism in Tai'an.